Catalytic reductive N-alkylation of amines using carboxylic acids - Andrews, Keith Gordon; Summers, Declan; Donnelly, Liam; Denton, Ross Matthew (Royal Society of Chemistry, 2015)
We report a catalytic reductive alkylation reaction of primary or secondary amines with carboxylic acids. The two-phase process involves silane mediated direct amidation followed by catalytic reduction.